Effect of saw-dust - sea shell powder mixture on compressive strength of cement mortar - Liew, Parker Be Chuan (2014)
Industrial waste materials as well as the municipal waste materials like saw-dust and sea shells produced each day is having a drastic increases with the rapid development of the technologies. These materials have been considered as materials which will lead to the negative impact to the environment and human life quality as well. With the increase awareness on the problem, more acceptable technologies are highly demand to minimize the quantity of these unused waste materials. In this research, saw-dust and sea shells powder have been added into the cement mortar mixture at the proportion of 1%, 2%, 3% and 4% to study the effect of these cement replacement materials on the workability of the fresh cement mortar and the compressive strength of the cement mortar cube at the ages of 7 days, 28 days and 56 days. Laboratory testing results showed the decrease in workability and compressive strength with the increase in the cement replacement materials. The compressive strength of the cement mortar was lower at the early curing age but improved significantly until the curing age of 56 days. From the testing, it had revealed that cement mortar with 1% of the cement replacement materials is adequate to have the maximum benefit in the gaining of the strength.